The Development of Project-based Learning Instrument Assisted by Lego® Mindstrom® - Puspitasari, Dara; Indratno, Toni Kus (Impulse: Journal of Research and Innovation in Physics Education, 2021)
An alternative solution to using STEM (Science, Technology, Engineering, and Mathematics) in learning is - by offering relevant contextual learning and integration of STEM knowledge via project-based learning with an educative robot kit as the learning instruments. This research developed a project-based learning instrument assisted by Lego® Mindstorm®, implemented by teachers in a physics lesson, specifically on friction material. The research's novelty dealt with the use of Lego® Mindstorm® as the visual aid with the STEM approach. This research used Borg & Gall's Research & Development model, consisting of 10 stages. The researchers focused this R&D only on student worksheets and lesson plans. In this research, the researchers involved five experts in judging the reliability of the learning instruments: the student worksheet and lesson plan applied in the learning process. The validation result of the developed student worksheet showed that the reliability judgment of material expert was 94.6%, while the expert of media with 79.7%. Then, the lesson plan's validation result was 76% based on the material expert's judgment. Then, the validation result of the evaluation instrument indicated an excellent category. Thus, the learning instruments were reliable to be implemented in the classroom to facilitate teachers in optimizing the learning technology.